Application of Additional Criminal Punishment of Dismissal from Military Service Against TNI Soldiers Proven to Commit the Crime of Same-Sex Indecency - Achmad Tamzil Adikara; Potler Gultom; Sujono Sujono (JURNAL HUKUM SEHASEN, 2023)
The phenomenon of LGBT groups is not only endemic in society within the TNI has also been some who joined the LGBT group where this group has damaged the identity of a firm attitude, discipline and soul sapta marga a faded due to LGBT groups. How is the regulation of same-sex immoral crimes (homosexual) in Indonesian criminal law? And How is the application of additional punishment of dismissal from military service against TNI Soldiers who are proven to have committed same-sex immoral crimes (homosexual) based on the legal considerations of the Judges in the Military Court Decision III-12 Surabaya Number 24-K / PM.III-12 / AD / II / 2020? The Regulation of Same-Sex Indecent Crimes (Homosexual) in Indonesian Criminal Law, there are differences in the regulation of same-sex indecent crimes between the old Criminal Code and the new Criminal Code. Where in the old Criminal Code, there was a disparity related to the age of the perpetrators of same-sex immoral crimes. Whereas in the new Criminal Code it is no longer regulated related to age. The application of additional punishment of dismissal from military service against TNI Soldiers who are proven to have committed same-sex immoral crimes (homosexual) is in accordance with applicable law. Because same-sex immoral acts are serious crimes, the defendant is given an additional sanction in the form of dismissal. This research uses the research method of Normative Juridical research method with secondary data consisting of premier, secondary and tertiary legal materials. Arrangement of Same-Sex Indecent Crimes (Homosexual) in Indonesian Criminal Law, there is no explicit prohibition in the Criminal Code related to indecent acts (homosexual) and not in accordance with the norms of decency, because same-sex indecent crimes are not prosecuted except on complaints, even though homosexual crimes have violated the norms of decency, and arrangements should be made related to the prohibition of homosexuality in the law. The application of additional punishment of dismissal from military service against TNI soldiers who are proven to have committed same-sex immoral crimes (homosexual) needs to be socialized so that soldiers are careful in maintaining their actions so that the honor of TNI soldiers is maintained.